Phenotypic plasticity raises questions for taxonomically important traits: A remarkable new Andean rainfrog (Pristimantis) with the ability to change skin texture - Guayasamín, Juan (2015)
We describe a new frog, Pristimantis mutabilis sp. nov., from the Andes of Ecuador. Individuals of the new species are remarkable for their ability to change skin texture from tuberculate to almost smooth in a few minutes, being the first documented amphibian species to show such dramatic phenotypic plasticity. The new taxon is assigned to the P. myersi group. It differs from other members of its group by body size (adult males 17.2-17.4mm; adult females 20.9-23.2mm), arboreal habitat, and red flash coloration in females. We document three call types for the new species, which differ through their number of notes and amplitude peaks. The three types are pulsed calls that share a dominant frequency of 3186.9-3445.3Hz. Surprisingly, we also document similar skin texture plasticity in species (P.sobetes) from a different species group, suggesting that this ability might be more common than previously thought. The discovery of these variable species poses challenges to amphibian taxonomists and field biologists, who have traditionally used skin texture and presence/absence of tubercles as important discrete traits in diagnosing and identifying species. Reciprocal monophyly and genetic distances also support the validity of the new species, as it has distances of 15.1-16.3% (12S) and 16.4-18.6% (16S) from the most similar species, Pristimantis verecundus. Additionally, each of the two known populations of Pristimantis mutabilis are reciprocally monophyletic and exhibit a high genetic distance between them (5.0-6.5%). This pattern is best explained by the presence of a dry valley (Guayllabamba River) that seems to be acting as a dispersal barrier. © 2015 The Linnean Society of London.